2015
DOI: 10.1097/inf.0000000000000582
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Burden of NDM-1 Positive Infections in Pediatric and Neonatal Patients in Pakistan

Abstract: In a neonatal/pediatric Gram-negative infection study from Islamabad, 71/82 strains were carbapenem resistant with 12/82 positive for New Delhi Metallo-β-lactamase and many being extensively antibiotic resistant. Burden and outcome analysis on 9 patients showed that 4/9 died after inadequate therapy regardless of organism type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…Internationally, Greece, Italy, the United Kingdom (UK), China, Pakistan, and Turkey have all described similarly small case series of CRE in children, with findings corroborating those from US studies [41–45, 50 53]. A report from Italy identified 15 CP-CRE isolates, of which 6 were associated with clinical infection, including 4 bacteremias and 2 UTIs.…”
Section: Epidemiology and Risk Factorssupporting
confidence: 55%
See 1 more Smart Citation
“…Internationally, Greece, Italy, the United Kingdom (UK), China, Pakistan, and Turkey have all described similarly small case series of CRE in children, with findings corroborating those from US studies [41–45, 50 53]. A report from Italy identified 15 CP-CRE isolates, of which 6 were associated with clinical infection, including 4 bacteremias and 2 UTIs.…”
Section: Epidemiology and Risk Factorssupporting
confidence: 55%
“…Patient-level risk factors for CRE infection in children include underlying chronic medical conditions, invasive medical devices, frequent or prolonged hospitalizations, prior antibiotic exposure, age, and travel from endemic regions [6, 35, 36, 39–44, 46, 4850, 52, 53]. Neonates seem to be a particularly at risk group with several reported outbreaks of NDM-1-producing Enterobacteriaceae in the neonatal population in the Indian subcontinent [35, 37, 47, 51].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Another study from Pakistan testified that 37 out of 78 new-borns died due to infections caused by MDR-Acinetobacter spp., [11]. Qamar et al, conducted a study in Islamabad, Pakistan also reported 4/9 children died due to NDM positive isolates mainly of E. coli and K. pneumoniae [12]. Recently, Khan et al, from Karachi, Pakistan also reported that 22 with <1 month of age and 10 were elderly patients died due to bacteraemia and septicaemia which was mainly caused by NDM positive K. pneumoniae [13].…”
Section: Mortality Morbidity and Economic Burden Due To Antimicrobiamentioning
confidence: 99%
“…NDM producing bacteria notable K. pneumoniae and E. coli are major cause of morbidity and mortality in developing countries. Qamar et al reported 4/9 children died due to NDM producing bacteria [12]. Similarly, another study from Karachi, Pakistan also documented 57% mortality in neonates due to NDM producing bacteria mainly K. pneumoniae [13].…”
Section: Class B Carbapenemase Producing K Pneumoniaementioning
confidence: 99%
“…Previously, we reported that 4/9 pediatrics who had been hospitalized in Islamabad, Pakistan died due to NDM producing bacteria [4]. Recently, another study revealed that 57% and 60% adult and neonatal patients died respectively in Karachi, Pakistan and the chief pathogen was NDM-1 positive K. penumoniae [5].…”
Section: Introductionmentioning
confidence: 99%